Thalidomide for the treatment of gastrointestinal bleeding due to angiodysplasia in a patient with Glanzmann’s thrombasthenia - Bruno K.L. Duarte; Silvia M. de Souza; Carolina Costa-Lima; Samuel S. Medina; Margareth C. Ozelo (Hematology Reports, 2017)
Angiodysplasia is a frequent cause of persistent gastrointestinal (GI) hemorrhage in elderly patients. Although GI bleeding isn’t the most common manifestation in patients with bleeding disorders, when present, it represents a challenging complication. We describe a 62-year-old patient with Glanzmann’s thrombasthenia, who used thalidomide for severe and recurrent GI bleeding. For 6 months, the patient experienced temporary control of GI bleeding with thalidomide in a daily oral dose of 100 mg. The anti-angiogenic effects of thalidomide have recently been explored by several groups, particularly in the management of bleeding from angiodysplasia, including cases with von Willebrand disease. Here, we review the relevant descriptions of the use of thalidomide in this situation, and also discuss potential reasons why we observed only a temporary control of the GI bleeding in our patient, such as the use of low-dose regimen due to limitations posed by thalidomide side effects.